Eucalyptus globulus Labill. Mediated synthesis of ZnO nanoparticles, their Optimization and characterization - Momina Shahid; Nimra Ijaz; Breera Shahid; Tabussam Tufail; Huma Bader Ul Ain; Muzzamal Hussain; Shahnai Basharat; Ali Ikram; Entessar Al Jbawi (Cogent Food & Agriculture)
In recent decades, nanotechnology has garnered significant attention for its diverse applications. Zinc Oxide (ZnO) nanoparticles (NPs) biosynthesized using plant extracts as both reducing and capping agents offer versatile solutions to various biological challenges. This study aimed to advance ZnO nanoparticle synthesis using a low-toxicity, cost-effective phytochemical method employing Eucalyptus globulus leaf extracts. Optimization of key factors (time, temperature, plant extract volume, and reagent concentration) was conducted to achieve high yield, stability, and controlled size. Optimal conditions were determined as 4hours, 60°C, 1:1 ratio, and 1mM concentration. Characterization of the synthesized ZnO NPs was performed through UV-visible spectroscopy, Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and Energy Dispersive X-ray Diffraction (EDAX). UV—visible analysis revealed a characteristic absorbance peak at 370nm, confirming ZnO NP formation. SEM affirmed the spherical ZnO NPs with a particle size of 25–151nm. EDAX demonstrated high purity, highlighting Zinc (Zn) and Oxygen (O) atoms. FTIR spectroscopy identified key phytochemical bands, elucidating the nanoparticle’s ability to reduce Zn ions, including polyphenols (3739.97cm-1), surface hydroxyl groups (3419.79cm-1), and C-OH stretching (1575.84cm-1). As a result of this research, nanoparticle synthesis can be made eco-friendly and economically viable, making it useful for environmental and industrial purposes.